PROFITABILITY RATIO ANALYSIS PROFIT GROWTH PT. GUDANG GARAM TBK ON THE IDX FOR THE 2014-2021 PERIOD - Abdul Karim; Indah Syamsuddin; Asrianto Asrianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the effect of ROA, ROE, and NPM on the profit growth of cigarette manufacturing companies on the IDX for the period 2014-2021. This study uses the method of analyzing the relationship between the independent variables and the dependent variable with descriptive statistical analysis, multiple linear regression, assumption test, and hypothesis testing. The results of the study partially identified that ROE on profit growth had a significant effect at 2.221 and a p-value of 0.035. ROE on profit growth is not significant and negative at -1.593 and p-value 0.122. While NPM has a significant and positive effect on profit growth at 4.740 and a p-value of 0.000. Net Profit Margin, Return On Assets, and Return On Equity affect profit growth using secondary data from the IDX. PT. Gudang Garam must evaluate the aspects of the profitability ratio, this is proven by ROE which hurts profit growth so that equity is correct so that all assets can be used efficiently so that profits are maximized.